2006
DOI: 10.1152/ajpendo.00364.2005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between insulin sensitivity and in vivo mitochondrial function in skeletal muscle

Abstract: Recent data have shown that individuals with low insulin sensitivity (S(I)) also have reduced whole body maximal oxygen uptake. The objectives of this study were to determine 1) whether muscle mitochondrial function was independently related to S(I) after being adjusted for known determinants of S(I) and 2) whether lower S(I) among African-American (AA) vs. Caucasian-American (CA) women was due to lower muscle mitochondrial function among AA women. Subjects were 37 CA and 22 AA premenopausal women (age: 33.6 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 46 publications
1
23
1
Order By: Relevance
“…National Health and Nutrition Examination Survey [NHANES], ACLS, and HERITAGE) does appear to indicate that increased aerobic capacity among non-Hispanic Black subjects provides significant protection from adverse cardiometabolic health outcomes, namely cardiovascular disease (CVD), type 2 diabetes, and some cancers [5,17,[21][22][23]. Although there is limited, direct evidence showing that low aerobic capacity causes racial health disparities, low aerobic fitness is associated with increased heart disease risk [49]. In addition, non-Hispanic Black subjects not only have lower aerobic fitness and insulin sensitivity than non-Hispanic White subjects but lower aerobic fitness was related to lower insulin sensitivity, suggesting that aerobic fitness might be involved with increased risk of developing diabetes in non-Hispanic Black subjects [6,7,49].…”
Section: Obesity and Aerobic Capacity In African Americansmentioning
confidence: 99%
See 1 more Smart Citation
“…National Health and Nutrition Examination Survey [NHANES], ACLS, and HERITAGE) does appear to indicate that increased aerobic capacity among non-Hispanic Black subjects provides significant protection from adverse cardiometabolic health outcomes, namely cardiovascular disease (CVD), type 2 diabetes, and some cancers [5,17,[21][22][23]. Although there is limited, direct evidence showing that low aerobic capacity causes racial health disparities, low aerobic fitness is associated with increased heart disease risk [49]. In addition, non-Hispanic Black subjects not only have lower aerobic fitness and insulin sensitivity than non-Hispanic White subjects but lower aerobic fitness was related to lower insulin sensitivity, suggesting that aerobic fitness might be involved with increased risk of developing diabetes in non-Hispanic Black subjects [6,7,49].…”
Section: Obesity and Aerobic Capacity In African Americansmentioning
confidence: 99%
“…Although there is limited, direct evidence showing that low aerobic capacity causes racial health disparities, low aerobic fitness is associated with increased heart disease risk [49]. In addition, non-Hispanic Black subjects not only have lower aerobic fitness and insulin sensitivity than non-Hispanic White subjects but lower aerobic fitness was related to lower insulin sensitivity, suggesting that aerobic fitness might be involved with increased risk of developing diabetes in non-Hispanic Black subjects [6,7,49]. Despite the rising obesity rates among non-Hispanic Black women, and their greater risk for several cardiovascular and related diseases, negative health outcomes resulting from low aerobic capacity in this population are not well described in the literature.…”
Section: Obesity and Aerobic Capacity In African Americansmentioning
confidence: 99%
“…Furthermore, in vivo magnetic resonance spectroscopy (MRS) measurements of basal mitochondrial ATP synthesis rates (16)(17)(18) and post-exercise phosphocreatine (PCr) (19) and ADP (20) recovery kinetics also point towards a potential role for mitochondrial dysfunction in the aetiology of insulin resistance and/ or type 2 diabetes. However, it was recently shown that in vitro mitochondrial respiration of permeabilized muscle fibres from biopsies of the type 2 diabetes patients and healthy controls did not differ between groups when the data were normalized for mitochondrial DNA content or citrate synthase activity (21).…”
Section: Introductionmentioning
confidence: 99%
“…Overweight African-American (AA) women are more hyperinsulinemic and resistant to insulin's glucoregulatory actions than body fat-matched Caucasian (C) women ( 5,6 ). Thus, it is logical to postulate that AAs may also exhibit higher rates of lipolysis and resistance to the antilipolytic effect of insulin.…”
mentioning
confidence: 99%